A Review on Performance Analysis of Matrix Converter Fed AC Motor Drive - Sri Vidhya Dhandapani; Venkatesan Thangavel (Institute of Advanced Engineering and Science, 2016)
This paper presents a review on the analysis of characteristics that determines the performance of the matrix converter fed AC motor drive. Review is made based on the analysis of the different characteristics achieved in the literature. Different characteristic parameters considered in this paper are total harmonic distortion, common mode voltage, voltage transfer ratio and efficiency. Comparison and analysis of these characteristic parameters is done based on various semi conductor switches, topology, and control and modulation techniques.